On the transition criterion to the regular cellular structure of a binary melt crystallization front - Kanischev, V.N.; Barannik, S.V. (Functional Materials, 2009)
The effect of regular cellular structure formation at a binary melt crystallization has been considered in the frame of the bidimensional solidification model under account for the surface energy of the liquid/solid phase interface. The transition to the phase interface with bulges arranged periodically thereon takes place at the crystallization speed value exceeding twice that causing the formation of the concentration supercooling zone in the melt. The calculated results are compared with the experimental data taken from literature. Варіаційним методом в рамках двовімірної моделі твердіння с урахуванням поверхневої енергії межі рідкої та твердої фаз досліджено ефект утворення регулярної комірчастої структури при кристалізації бінарного розплаву. Показано, що перехід до міжфазної межі з періодично розташованими на ній виступами відбувається при швидності кристалізації, яка вдвічі перевищує її значення, при якому в розплаві з'являється зона концентраційного переохолодження. Проведено зіставлення результатів обчислення з наявними в літературі експериментальними даними. Вариационным методом в рамках двумерной модели затвердевания с учетом поверхностной энергии границы жидкой и твердой фаз исследован эффект образования регулярной ячеистой структуры при кристаллизации бинарного расплава. Показано, что переход к межфазной границе с периодически расположенными на ней выступами происходит при скорости кристаллизации, в два раза превышающей ее значение, при котором в расплаве появляется зона концентрационного переохлаждения. Проведено сравнение результатов расчета с имеющимися в литературе опытными данными.